Outcome of Minimal Invasive Percutaneous Plate Osteosynthesis in closed fractures of distal tibia - Mishra, Anil K; Chalise, PK; Shah, SB; Adhikari, V; Singh, RP (Journal of College of Medical Sciences-Nepal, 2014)
Background: The limited soft tissue, subcutaneous location and poor vascularity render the dista tibial fractures very challenging. Treatment of distal tibial fractures using minimally invasive percutaneous plate osteosynthesis technique may minimise damage to soft tissues and vascular integrity of bony fragments, leaving comminuted fragments out of the mechanical construct, preserving soft tissues with limited operative exposure. Objective: To assess the outcome of patients treated with minimally invasive percutaneous plate osteosynthesis technique for closed distal tibial fractures. Methods: The study included total of 30 patients (24males and 6females) with close distal tibia fracture, which were treated with distal tibia locking plate using minimally invasive percutaneous plate osteosynthesis technique. Results: The mean ages of the patient were 44.23 years (30 to58 years). Patients were followed up at 2 weeks, 6weeks, 12weeks, 24weeks and 1 year after the operation and evaluated clinically and radiologically. Among 30 pateints, all fractures went to union. The mean American orthopaedic foot and ankle score was 89.23% (SD-3.92). There was 2case of superficial infection and 3 case of plate impingement with no intraoperative complication and mortality rates. Conclusion: Minimally invasive percutaneous plate osteosynthesis is an effective technique for the management of distal tibial fractures. It is minimally invasive, though technically demanding, but preserves the biological environment by preserving the soft tissue with better outcome in terms of radiological union and functional outcome. Journal of College of Medical Sciences-Nepal, 2013, Vol-9, No-2, 38-44 DOI: http://dx.doi.org/10.3126/jcmsn.v9i2.9686